Application of the HFACS-PV approach for identification of human and organizational factors (HOFs) influencing marine accidents. (April 2021) - Yildiz, Serdar; Uğurlu, Özkan; Wang, Jin; Loughney, Sean
Highlights: In this study, the feasibility of the modified Human Factor Analysis and Classification System for Passenger Vessel collisions (HFACS-PV) is demonstrated for other types of accidents. The HFACS-PV structure makes it possible to evaluate the occurrence of marine accidents and to analyse the contributions of human error. The results of this study show that the HFACS-PV structure is compatible with contact, grounding and sinking accidents as well as collisions. The main feature that distinguishes HFACS-PV from other HFACS structures is that it examines the internal and external environmental factors as a separate level under the name "Operational Conditions" Abstract: Shipping is one of the leading modes of transport that has dominated the world economy from past to present. The effectiveness and efficiency of maritime trade is closely related to maritime safety. Providing quality maritime safety is a fundamental requirement for environmentally friendly, sustainable, safe and efficient global trade. Therefore, maritime safety and human factors are frequently studied topics in literature. However, the fact that the human element has a complex socio-technical structure makes it difficult to fully analyse human factors in accidents. That is one of the biggest challenges in preventing and mitigating accidents. This research aims to demonstrate the feasibility of the modified Human Factor Analysis and Classification System for Passenger Vessel collisions (HFACS-PV) for other types of accidents. 51 grounding accidents that occurred in passenger vessels between 1991 and 2017 were analysed by using the HFACS-PV structure. The results show that the HFACS-PV structure created for passenger vessel accidents is compatible with contact, grounding and sinking accidents as well as collisions. Thus, the HFACS-PV structure allows for coherent analysis of marine accidents. Owing to the flexibility of HFACS, it is also possible to combine it with other analytical methods to conduct both qualitative and quantitative analysis.